2018
DOI: 10.1111/his.13448
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumours of bone treated with denosumab: histological, immunohistochemical and H3F3A mutation analyses

Abstract: Denosumab therapy effectively decreases the number of osteoclastic cells in GCTBs. However, the neoplastic cells with H3F3A mutation survive denosumab treatment and undergo dramatic histological changes in response to this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
(48 reference statements)
3
33
0
2
Order By: Relevance
“…We analyzed both G34W and SATB2 stains in pre-and post-denosumab-treated GCTB, and our results showed a significant reduction in the number of G34W-positive mononuclear cells in post-denosumab tumors (mean 68.9% in pretreatment to 26.9% in posttreatment) that was statistically significant (P = .001). Results of other 2 studies, 24,25 however, did not show significant difference in the expression of G34W in pre-and posttreatment specimens. The most recent study by Treffel et al 25 found that H3.3 G34W expression (mean index from 55% before denosumab to 47% after denosumab) was statistically significant (P = .06).…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…We analyzed both G34W and SATB2 stains in pre-and post-denosumab-treated GCTB, and our results showed a significant reduction in the number of G34W-positive mononuclear cells in post-denosumab tumors (mean 68.9% in pretreatment to 26.9% in posttreatment) that was statistically significant (P = .001). Results of other 2 studies, 24,25 however, did not show significant difference in the expression of G34W in pre-and posttreatment specimens. The most recent study by Treffel et al 25 found that H3.3 G34W expression (mean index from 55% before denosumab to 47% after denosumab) was statistically significant (P = .06).…”
mentioning
confidence: 56%
“…We found a mean of 68.8% G34W-positive cells in the pretreatment specimens as compared with a mean of 26.9% cells in post-denosumab cases. Kato et al 24 also observed decreased number of G34W+ cells in post-denosumab specimens as compared with pretreatment specimens. Traub et al 18 performed immunohistochemical stains RANK and RANKL on 20 pre-and post-denosumab cases of GCTB.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations